ANALYSIS OF CONSTRUCTION-RELATED FACTORS AFFECTING THE EFFICIENCY OF CONSTRUCTION LABOUR - Oluseyi J. ADEBOWALE; Ayodeji J. FAPOHUNDA (Journal of Construction Project Management and Innovation)
Irrespective of significant relevance of construction industry to economic growth of developed and developing nations, labour efficiency in the construction industry remains relatively low and thus affects construction project delivery and client’s satisfaction. This paper aims at exploring adverse construction related factors contributing to the shortfall of construction labour efficiency in the South African construction industry. The study adopts mixed methodological approach, administering closed ended questionnaires to construction professionals on Western Cape and Gauteng construction sites, while experienced construction site supervisors were interviewed to validate quantitative data obtained. Statistical Package for Social Sciences (Version 22) and content analysis were used respectively to analyse data obtained. Communication ability of site managers, construction skills of site supervisors and effective site planning ability of contractors were found as the predominant construction related factors affecting the efficiency of construction labour. This study is restricted to contractors, site supervisors and site managers’ related factors affecting the efficiency of construction labour. Adequate application of findings presented in this study will significantly reduce the current prevalent construction time and cost overruns through an improved construction workforce performance. Enhanced construction productivity is a product of construction labour efficiency that ensures achievement of construction project objectives and heightens contribution to South African economic development.